A Computational Study About The Effect Of Surface Shape On Strength & Stiffness Of Tensioned Fabric Structures Under Wind Loading - Kuan, Hui Myen (Universiti Sains Malaysia, 2006)
This thesis is carried out to investigate the effect of surface shape on strength (in terms of maximum stress) and stiffness (in terms of surface displacement) of tensioned fabric structures under wind loading. In this paper, anticlastic forms like saddle, cone and membrane dome of tensioned fabric structures were analyzed. Finite element software – ADINA is used to create the models of tensioned fabric structure. It is followed by analyzing step by using a stress analysis computer program to investigate the form as well as the effect of wind loading for each model with different pre-stress level conditions under the same wind loading condition. From the study, the location of maximum stress and displacement of different shape is recognized in order to check the efficiency of different shapes in resisting wind loading. The graph of maximum tension/pre-tension versus sag/span is used to show the relationship between structure strength and effect of wind loading. While the graph for percentage of maximum displacement versus pre-tension is used to show the relation between the shape and the stiffness of the structure. This study has covered rectangular saddle surface, square saddle surface and conical surface for both strength and stiffness of the surface shape mentioned above. It has been found that the square saddle surface exhibits the best result to resist wind loading. This conclusion is based on the lowest ratio for maximum tension/pre-tension and sag/span as well as the lowest percentage for displacement result exhibited in the result for square saddle surface. The outcome of the study will provide technical guidance on efficiency of different shapes of tensioned fabric structures in resisting wind loading.